(untitled) (One Health & Risk Management, 2021)
Introduction. On January 31, 2020, the World Health Organization declared a Public Health Emergency of International Interest caused by a new type of Coronavirus infection. By the Order of the Minister of Health, Labor and Social Protection no. 188 of February 26, 2020, the Algorithm of measures regarding the supervision of healthy persons and persons with clinical signs of disease was implemented. On the basis of the above-mentioned order, by order of the Minister of Defense in March 2020 was implemented „Instruction on measures to reduce the risk of spreading cases of infection with the new type of Coronavirus (COVID-19) in the National Army”. In addition to the basic function, Outpatient Clinic is response to conduct medical examination for conscript soldiers during the accommodation period and to conduct pre-and post-deployment medical examination for International Peacekeeping Operations/ Missions. The evolution of the epidemiological situation in the Republic of Moldova and in the National Army created a necessitation to adjust the activity of the Outpatient Center of the Ministry of Defense in conditions of COVID-19 pandemic. The purpose of the study is based on the recommendations, regarding the prevention and control of the spread of the SARS CoV-2 virus, to develop proposals for strengthening the capacities of the Outpatient Center, in accordance with the pandemic situation caused by the SARS CoV-2 virus. Material and methods. The study is based on the narrative synthesis of bibliographic sources, which include international and local references, normative basis and statistical data. The materials include the recommendations of the World Health Organization, Order of the Ministry of Health, Labor and Social Protection, and decision of the Extraordinary Public Health Commission. Results. By Order of the Minister of Defense no. 155/2020, "Instruction on how to address the military for medical assistance in case of suspect or patient with" Coronavirus of the new type COVID-19" was implemented. The Outpatient Center shifted to a special activity regime under COVID-19 pandemic conditions. Special medical team was created to collect samples for testing suspects/patients within medical institution and at home. Patients with positive test results and minor clinical signs were given treatment at home under daily supervision. Military individuals with severe signs were transported to the Military hospital of the Ministry of Defense by ambulance or Emergency Service „112”. The newly recruited soldiers underwent additional medical examination in the first days after enrolment. In September 2020, the medical examination was carried out on the students from the Military Departments. During the pandemic, medical examination was carried out for military personnel of the National Army for participation in International Peacekeeping Operations (IPKO). Mention medical examinations to assess fitness for military service in IPKO was organized in compliance with measures to prevent and spread the infection. In March 2021, based on the Order of the Ministry of Health, Labor and Social Protection no. 93 of February 5, 2021 on the implementation of the National anti-COVID-19 immunization Plan, an Outpatient Clinic was created as a vaccination center for the anti-COVID-19 immunization of personnel of Ministry of Defense and the civilians registered with the family doctor from clinic. Conclusions. For the efficient organization of the activity of the Outpatient Center under pandemic conditions, it is necessary to adjust: (1) Rules of supply with material and medical means Medical Treatment Facility of Ministry of Defence, (2) Medical Support Plan in Operations.